The RADEC: Improving Reading Comprehension and Self-Regulated Learning in Elementary School - Hervianti, Wiwiet; Cahyani, Isah; Sopandi, Wahyu (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
RADEC: Improving This research aims to investigate and analyze the effectiveness of using the RADEC learning model in improving reading comprehension and self-regulated learning (SRL) in elementary school students. The research method used in this research is literature study, which involves searchizg, selecting, and synthesizing information from various relevant literature sources. The results of literature research show that the RADEC learning model has the potential to improve reading comprehension and SRL abilities in elementary school students. The syntax of the RADEC model, such as Read, Answer, Discuss, Explain, and Create, has been proven to be effective in improving students' reading comprehension and SRL. In addition, this literature review also reviews previous studies that have implemented the RADEC model in the context of elementary school education and demonstrated significant improvements in students' reading comprehension. It is hoped that this research can contribute to the development of an effective and relevant RADEC learning model for elementary schools and open the door for further research exploring the potential of this learning model in improving reading comprehension and SRL at the basic education level.